Modelling of urban goods vehicles movement in Singapore - Ramachandran Pillai Sreekumar (2008)
This study aims to review various methods for goods or freight modeling and analysis in Singapore. It proposes an appropriate truck trip distribution model using gravity model analysis that can be useful for studying the goods distribution in Singapore.